(untitled) (Research, Society and Development, 2024)
Sleep is understood as a natural process of reduction of the body’s response to external stimuli, associated with the loss of consciousness, which is useful for several functions. However, there is currently an increase in the number of individuals who do not achieve a good sleep routine, which can be attributed to an increase in exposure to factors that hinder the achievement of adequate time and quality of sleep, leading to various impacts that affect cognitive health and the processes of knowledge acquisition and consolidation. Thus, it aims to clarify the mechanisms associated with sleep deprivation and its repercussions on memory and learning. It is a literature review based on the analysis of scientific articles published from 2012 to 2022, in PubMed and Science Direct, in which the key words "sleep deprivation" AND "memory" AND "learning" were used. It was verified that sleep deprivation can impair several cognitive and affective functions, such as reduced attention, psychomotor vigilance and increased variability in behavioral responses. In relation to memory processing, the decrease of the quantity and the quality sleep time can affect the ability to retain new information and make individuals more prone to develop false memories. Therefore, realizing the fundamental role of sleep in several functions of the human body, highlighting the consolidation of memory and learning, understand the various unfavorable impacts that a reduction in the number and quality of hours of sleep can have.